Respon Fisik dan Konsentrasi Belajar Siswa Kelas IV dalam Program Senam Anak Indonesia Hebat: Penelitian - Siane Maria Tampi; Fazryani Mazita Torano; Dodi Fansi Patty (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Physical education in elementary schools is crucial for developing physical fitness, healthy habits, and cognitive skills. The Senam Anak Indonesia Hebat (SAIH) Program aims to promote an active lifestyle and improve learning abilities among children through enjoyable, age-appropriate movement activities. However, limited empirical data exist on its effectiveness, particularly in Heram District, Jayapura City. This study addresses the gap by examining the impact of SAIH on physical responses and learning concentration among Grade IV students at SDN Inpres Bertingkat Waena. Using a quantitative descriptive method, 30 students were purposively sampled. Physical responses were measured through heart rate monitors and activity observations, while concentration was assessed with age-appropriate tests. Data analysis involved descriptive statistics and correlation analysis. Results showed a significant reduction in heart rate (from 98.3 to 86.7 bpm) and respiratory rate (from 25.1 to 20.9 breaths per minute), alongside a notable increase in concentration scores (from 62.4 to 78.6). A negative correlation between physiological measures and concentration indicates that improved physical stability supports better learning focus.